Study and analysis of switching transients in high voltage transmission line - Ahmed, Prottasha; Faiyaz, Alif Fatin; Gupta, Anik Das; Rashid, Hisham -Al- (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.